The role of POKDARWIS on homestay digital marketing: A case study in South Sulawesi’s tourist villages - Ohyver, Daniel Adolf; Azinuddin, Muaz; Mat Son, Ahmad Puad (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2025)
Tourism villages in Indonesia leverage Community-Based Tourism (CBT) to foster rural development, with homestays serving as a key economic driver. However, limited digital resources hinder effective marketing in remote areas. This study explores the role of Tourism Awareness Community Groups (POKDARWIS) in enhancing homestay digital marketing in Barania and Campaga villages, South Sulawesi. Using a qualitative case study approach, data were gathered through in-depth interviews with POKDARWIS members, homestay managers, and tourists, supplemented by observations and document analysis. Thematic analysis revealed POKDARWIS’s multifaceted contributions, including booking coordination, digital content creation, capacity-building training, and collaboration with local stakeholders. Social media and village websites improved homestay visibility and tourist arrivals. However, challenges such as low digital literacy, resource constraints, and funding gaps persist. The findings underscore POKDARWIS’s dual role as both a marketing facilitator and a community empowerment agent, advancing sustainable tourism. The study recommends stronger government support, targeted training, and partnerships to optimize digital marketing outcomes. By demonstrating how grassroots organizations harness digital tools, this research enriches CBT literature and offers practical insights for inclusive rural tourism development.